Woshentliches Kindschaftsblatt des Herzogthum Krain (1775 - 1776). Balthasar Hacquet as journalist - Žigon, Tanja (Hacquetia, 2015)
The Society for Agriculture and Useful Crafts of Carniola published an economic paper, entitled Woshentliches Kindschaftsblatt des Herzogthum Krain (The proclamations' weekly of the Duchy of Carniola from January 1775 to December 1776). It's editor was Balthasar Hacquet, Society's secretary.